The teleology of the sign user - Almen, Byron (Interdisciplinary Studies in Musicology, 2018)
In my 2009 book A Theory of Musical Narrative, I argued that narrativity in music can be productively understood according to the principle of transvaluation as defined by the American semiotician James Jakob Liszka. An important aspect of this principle — and hence of musical narrative — is what Liszka describes as “the teleology of the sign user”: that is to say, the critical role played by the interpreter’s cognitive, cultural, and ideological perspective in formulating and presenting an interpretation. When this role is considered at all, it is frequently confined to a general, cautionary usage wherein the notion of a single, “correct” narrative interpretation of a work is repudiated and a sensitivity to context encouraged. In this chapter, I attempt to move beyond this general usage to consider ways in which it might be more fully characterized and formalized. To that end, I consider certain interpretive perspectives that might be characterized as possessing a cognitive (as opposed to a situational or cultural) component and understood within a framework of binary oppositions. In particular, I call attention to the fundamental formative roles that such perspectives can play in shaping and directing interpretive details. For example, the perception of — and hermeneutic engagement with — patterns deemed to be of narrative significance can arise either from a bounded (or centripetal) perspective, in which case the interpretive details tend to reinforce one another, circling around a relatively unified and coherent narrative, or they can arise from an unbounded (or centrifugal) perspective, in which case the interpretive details tend to push outward, suggesting the possibility of other non-selected yet viable alternative narratives. These and other binary formulations to be discussed are applied to musical narratives but also have implications for narrative interpretation in general.